Debt underwriting by commercial bank-affiliated firms and investment banks: More evidence - Roten, Ivan C; Mullineaux, Donald J (Journal of Banking & Finance, 2002)
We compare underwriting performance by commercial bank-affiliated firms (Section 20s) and traditional investment banks over the period 1995–1998. We find that gross spreads are lower in the case of Section 20 underwritings, but that yield spreads are not. Our sample includes a substantial number of observations following changes in Federal Reserve policies that substantially eased restrictions on Section 20 activities in early 1997. Our findings differ somewhat from results in the literature that focused on periods prior to these policy changes. We find, for example, no evidence that a prior commercial bank lending relationship influences underwriting yields for any type of issue. Our results also fail to confirm earlier evidence that collective Section 20 underwritings produce a favorable competitive effect on gross spreads and yield spreads. We find substantial evidence that both the underwriting mix and the underwriting process are relevant to the behavior of gross spreads and yield spreads over the sample period.